Examination of a Chinese-made cryptococcal glucuronoxylomannan antigen test in serum and bronchoalveolar lavage fluid for diagnosing pulmonary cryptococcosis in HIV-negative patients - Li, Zhengtu; Wang, Mingdie; Zeng, Peiying; Chen, Zhaoming; Zhan, Yangqing; Li, Shaoqiang; Lin, Ye; Cheng, Jing; Ye, Feng (Journal of microbiology, immunology and infection, 2022)
We presented the performance of a Chinese-made cryptococcal glucuronoxylomannan (GXM) antigen test using serum and bronchoalveolar lavage fluid (BALF) samples in the HIV-negative Chinese population. Between February 2017 and January 2019, HIV-negative patients with pulmonary cryptococcosis were recruited and followed-up every three months, including completion of a chest CT examination and collection of serum and BALF samples. Here, thirty-seven confirmed and ten clinically diagnosed patients were recruited. Furthermore, samples from 174 noncryptococcosis patients that may cause false positives were also collected. The sensitivity of a lateral flow assay (LFA) for detecting cryptococcal GXM antigen in serum and BALF samples from confirmed cases was 97% and 95%, respectively, and the specificity was 98.2% and 93%, respectively, and the differences in these values between the BALF and serum samples were not significant. The serum cryptococcal GXM antigen value showed a positive correlation (r: 0.581, p < 0.001) with pulmonary lesion size, while the BALF value showed no correlation (r: 0.253, p: 0.13). The positivity rate of BALF was higher than that of serum when the diameter of the pulmonary lesion was small (diameter less than 20 mm). Moreover, the serum cryptococcal GXM antigen levels showed an overall decreasing trend with the decrease in pulmonary lesion size after antifungal therapy in patient follow-up. The Chinese-made cryptococcal GXM antigen test has better sensitivity and specificity for diagnosing pulmonary cryptococcosis in the HIV-negative Chinese population, and it could be used to diagnose and to monitor this disease.